2015
DOI: 10.12944/cwe.10.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Groundwater Quality with Seasonal Fluctuation in Jharia Coal Mine Region, Jharkhand, India

Abstract: Jharia coal mining areas is one of the most important coal mining area in India. It is roughly elliptical or sickles -shaped, located in Dhanbad district of Jharkhand. For the assessment of groundwater quality, Twenty Nine groundwater samples were collected from Jharia coalfield. The pH of the analysed water samples is slightly acidic to slightly alkaline in nature in both the season. In majority of the samples, the analyzed parameters are well within the desirable limits and water is potable for drinking purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Additionally, metal pollution indices, such as the contamination factor, degree of contamination, and heavy metal pollution index, were calculated to assess the overall surface water quality in the N'djili River watershed. This method is considered reliable and has been successfully used in other studies, including those by Mohan et al (1996), Prasad & Bose (2001), Tamasi & Cini (2004), Mahato et al (2014), Goher et al (2014), Tiwari et al (2015), Panigrahy et al (2015), Karaouzas et al (2011), Djade et al (2020), and Vualu (2020. Contamination Factor Hakanson (1980) proposed the use of the contamination factor as a single index.…”
Section: Sampling Methodsmentioning
confidence: 92%
“…Additionally, metal pollution indices, such as the contamination factor, degree of contamination, and heavy metal pollution index, were calculated to assess the overall surface water quality in the N'djili River watershed. This method is considered reliable and has been successfully used in other studies, including those by Mohan et al (1996), Prasad & Bose (2001), Tamasi & Cini (2004), Mahato et al (2014), Goher et al (2014), Tiwari et al (2015), Panigrahy et al (2015), Karaouzas et al (2011), Djade et al (2020), and Vualu (2020. Contamination Factor Hakanson (1980) proposed the use of the contamination factor as a single index.…”
Section: Sampling Methodsmentioning
confidence: 92%
“…
Figure 1 Location of coal samples in Jharia coalfield (Modified after Panigrahy et. al, 2015 29 and plotted using Golden Software Surfer 11.0.642).
…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the study of long wall mining operations of Greene (4 mines) and Washington county (3 mines) revealed that over the period of 2003e2008 affect 106 of 1214 undermined water supplies. Around 8.7% of these affected water supplies were within the 200 feet's of active mining sites [98]Similarly, another study conducted in Jharia coal mine region (India) had also shown instability in its water table [99]. Almost all of the tube wells in the mining area (Odrisha, India) dried during the summer season [100].…”
Section: Depression Of Water Table Around the Dewatered Zonementioning
confidence: 99%